Heavy metal accumulation in tomato and cabbage grown in some industrially contaminated soils of Bangladesh: Heavy metals in contaminated soils and vegetables (Journal of the Bangladesh Agricultural University, 2019)
Heavy metal accumulation in environmental compartments is a potential risk to the living system because of their uptake by plants and subsequent introduction into the food chain. A study was carried out to investigate the heavy metal contents in industrially contaminated soils collected from six different locations of Dhaka and Mymensingh districts and their effects on two important vegetables namely tomato and cabbage. Pot experiment was conducted using contaminated soils at the net house of Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh following completely randomized design (CRD) with three replicates. The higher level of heavy metal contents was found in the soil samples of Hajaribag and Dhaka Export Processing Zone (DEPZ). The highest Ni, Cd, Cr, Cu and Fe contents were 59.45, 18.79, 67.57, 40.81 and 1619.61 µg g−1 which were much above the recommended level except Cu contents. The highest yield of vegetables was obtained grown in Maskanda soil of Mymensingh district and the lowest from DEPZ soil of Dhaka. The highest Ni, Cr and Fe contents were 8.91, 7.22, 419.65 µg g−1, respectively in tomato fruits grown in the soil of Hajaribag whereas the highest Cu content (3.38 µg g−1) was obtained from Seedstore soil, Mymensingh and highest Cd content (2.88 µg g−1) was from Mitford ghat soil, Dhaka. In cabbage, the highest Ni (17.52 µg g−1) and Fe (411.25 µg g−1) contents were found in the soils of DEPZ whereas the highest Cr (9.17 µg g−1), Cd (3.52 µg g−1) and Cu (8.51 µg g−1) were obtained in the plants grown in the soils of Hajaribag, Mitford ghat and Maskanda, respectively. Concentrations of all the tested heavy metals except Cu in both vegetables were above the maximum allowable limit prescribed by the World Health Organization. Among the metals, the accumulation of Ni was found as higher amount (0.39 and 0.71 for tomato and cabbage, respectively) based on plant concentration factor or transfer factor. The results showed a positive correlation between concentration of the metals present in soils and in vegetables and the highest correlation was found with Cr in tomato and Fe in cabbage. However, both the soils and grown vegetables were consistently observed to pose a risk to human health. So, it can be recommended that government should take necessary action so that heavy metals used in the industries cannot come into the nearby agricultural field to ensure food safety as well as food security.J Bangladesh Agril Univ 17(3): 288–294, 2019